Isolation and characterization of indigenous Weissella confusa for in situ bacterial exopolysaccharides (EPS) production in chickpea sourdough. (December 2020) - Galli, Viola; Venturi, Manuel; Coda, Rossana; Maina, Ndegwa Henry; Granchi, Lisa
Graphical abstract: Highlights: Weissella confusa was isolated from chickpea spontaneous sourdough fermentation. Weissella confusa Ck15 produced dextran with 2.6% of α-(1 → 3) linked branches. 2% of sucrose, dough yield of 333, and 30 °C enhanced exopolysaccharides production. Microbial exopolysaccharides can be utilize to set up a chickpea based baked product. Abstract: Legume-based sourdough represents a potential ingredient for the manufacture of novel baked products. However, the lack of gluten of legume flours can restrict their use due to their poor technological properties. To overcome such issue, the in situ production of bacterial exopolysaccharides (EPS) during fermentation has been proposed. In this study, an EPS-producing lactic acid bacteria for in situ production in chickpea sourdough was isolated. After several backsloppings of the spontaneously fermented chickpea flour dough, a dominant strain of Weissella confusa was isolated and identified. W. confusa Ck15 was able to produce linear dextran with 2.6% α-(1 → 3) linked branches, from sucrose. Temperature of 30 °C, dough yield of 333, and 2% of sucrose addition were used to produce fermented chickpea sourdoughs. The acidification and rheology of the sourdoughs inoculated with W. confusa Ck15, Leuconostoc pseudomesenteroides DSM 20193, as positive control, and Lactobacillus plantarum F8, as negative control, were compared. The in situ dextran production by W. confusa Ck15 fermentation led to the highest viscosity increase (5.90 Pa·s) and the highest EPS percentage in the doughs (1.49%), compared to the other doughs. The in situ dextran production represents a potential approach for improving the use of legume flour in bakery products; overall, this experiment represents a first step for the exploitation of microbial EPS for setting up a baking process for chickpea based product.